Nephrocalcinosis in a portuguese pediatric population - Bota,Sofia (2019)
Introduction and Aims: Nephrocalcinosis is characterized by the deposition of calcium in the kidney parenchyma and tubules. The renal prognosis depends on the underlying cause, emphasizing the importance of its identification. We aim to review the data of children with nephrocalcinosis concerning etiology, clinical manifestations, growth and renal function at presentation and outcomes. Methods: Retrospective study of the records of children (<18 years) with nephrocalcinosis followed by a pediatric nephrology unit of level III hospital, between 2008-17. Clinical features, etiology, treatment and outcomes were evaluated. Results: We identified 35 cases: 24 isolated (69%) and 11 with nephrolithiasis (31%). The group was mostly constituted of girls (54%). Median age at presentation was 6 years (7 months - 17 years old); 40% of patients were under 2 years of age, 31% between 3 and 9 years and 29% older than 10 years. Mean follow-up was 4 years (1-9). The most common clinical manifestation was failure to thrive in the first year of life (34%) and flank or abdominal pain (20%); in 23% it was an incidental finding. Eleven percent of patients had a systemic syndromic disease. Renal function at diagnosis was normal in all children. The most frequent causes were metabolic abnormalities (23%), hereditary tubulopathies (23%), prematurity (20%) and pharmacologic (14%). Eleven percent were considered idiopathic. In a logistic regression analysis, sex, age of presentation and familiar history of nephrocalcinosis showed no correlation with nephrocalcinosis, nephrocalcinosis and nephrolithiasis or hereditary/metabolic etiologies. Discussion: Despite the small sample, in this study, the hereditary and/or metabolic disorders were the main cause of nephrocalcinosis. Associated symptoms and comorbidities, such as prematurity, growth retardation, intestinal malabsorption, or bone demineralization, should be evaluated for diagnostic purposes. No patient developed chronic kidney disease.